A novel reusable anti-COVID-19 transparent face respirator with optimized airflow - ÇAM, MUHAMMET EMİN (SPRINGER HEIDELBERG, 2021)
This novel face mask is designed to be a reusable respirator with a small and highly efficient disposable fabric filter. Respirator material requirements are reduced by 75% compared to traditional designs and allow repeated cleaning or sterilization. The probability of virus particle inhalation is reduced using novel air filtration pathways, through square-waveform design to increase filter airflow. Air enters the mask from right and left side filters, while the area in front of the mouth is isolated. Clear epoxy is used for a transparent frame, allowing lip-reading, and mask edges contain a silicone seal preventing bypass of the filters. The mask is manufactured using silicone molds, eliminating electricity requirements making it economical and viable in developing countries. Computational fluid dynamics numerical studies and Fluent ANSYS software were used to simulate airflow through the filter to optimize filter air path geometry and validate mask design with realistic human requirements. The breathing cycle was represented as a transient function, and N95 filter specifications were selected as a porous medium. The novel design achieved 1.2 x 10(-3)kg s(-1), 20% higher than human requirements, with air streamlines velocity indicating local high speed, forcing and trapping virus particles against filter walls through centrifugal forces.
Keywords: COVID-19; Mask; Prototype; Flow; Pressure; Temperature; COMPUTATIONAL FLUID-DYNAMICS; SIMULATION